Zakat Infak Sodaqoh sebagai Instrumen Pertumbuhan Ekonomi di Indonesia - Ermi Suryani (Fakultas Syariah IAIN Laa Roiba Bogor, 2020)
ABSTRACT This study aims to explore the potential of zakat, infaq, shodaqoh as a support for economic growth in Indonesia. The method used is a qualitative method through the study of literature and critical analysis. ZIS was able to increase economic growth in Indonesia year after year. The higher the level of Muslim awareness of paying zakat the greater the opportunity for Indonesia's economic growth. The infaq and alms are two things attached to zakat because it is not regulated in regulation in Indonesia. The existence of infaq and alms has a great opportunity to be managed productively so that the strategy in managing ZIS is something that must be analyzed thoroughly. The goal is that ZIS funds collected from muzakki can be utilized to improve the welfare of the community, especially Muslims in Indonesia. ZIS is not obliged to tackle poverty in Indonesia, but is able to reduce the government's burden on the welfare of the people. Amil is required to be creative in managing ZIS so that the criteria for amil need to be socialized and determined. Among them: first, qualified knowledge theoretically / practically in ZIS. Second, high social value and fond of entrepreneurship. Third, honest from small things to big things. Fourth, close to the community / easy to get along with all groups and always simple. Fifth, have many links with BAZNAS / BAZDA and LAZNAS. Keywords: amil, economy, Indonesia, infaq, shodaqoh, zakat,